Employee’s Well Being dan Job Satisfaction : Tinjauan Peran Family Supportive Supervisor Behaviors dan Work-Family Conflict - Moch Endaryanto; Puji Astuti (Journal of Management and Bussines (JOMB), 2024)
This research aims to explore the influence of family supportive supervisor behaviors on work-family conflict and its impact on work life balance and work engagement, which in turn influences employee job satisfaction. This research method used purposive sampling and involved 357 aircraft cabin crew from airlines in Indonesia. Data analysis was carried out using Structural Equation Modeling (SEM). The research results show that family supportive supervisor behaviors have a negative influence on work-family conflict. Furthermore, work-family conflict also has a negative influence on employee work-life balance and work engagement. However, work life balance and work engagement positively influence employee job satisfaction. The managerial implication of this research is that the implementation of family supportive supervisor behaviors in companies can help reduce the level of work-family conflict, so that employee performance and productivity can increase. Thus, companies can obtain long-term benefits through attention to these aspects. Conclusion, this research contributes to the understanding of the relationship between family supportive supervisor behaviors, work-family conflict, and employee work welfare factors. The practical implications of this research provide guidance for companies in developing management policies and practices that support balance between work life and personal life of employees, so as to increase overall job satisfaction and productivity. Keywords: Employee's Well-Being, Family Supportive Supervisor Behaviors, Job Satisfaction, Role Analysis, Work-Family Conflict